Achieving extraordinary structural efficiency in a wrought magnesium rare earth alloy. Issue 4 (2nd April 2020) - Panigrahi, S. K.; Mishra, R. S.; Brennan, R. C.; Cho, K.
ABSTRACT: The opportunities for wrought magnesium products in a wide range of structural and functional materials for transportation, energy generation, energy storage and propulsion are increasing due to their light-weighting benefits, high specific strength and ease of recyclability. However, the current uses of wrought magnesium alloys for structural applications are limited due to comparatively low strength, high yield strength asymmetry and poor formability & superplasticity. In the present work, we developed an ultrafine-grained magnesium alloy with an extraordinary strength and ductility combination, exceptional high specific strength, zero yield strength asymmetry and excellent high strain rate superplasticity. GRAPHICAL ABSTRACT: IMPACT STATEMENT: We have developed friction stir processed UFG microstructure in a rare-earth containing magnesium alloy and achieved exceptional strength-ductility combination along with no yield asymmetry and extraordinary high strain rate superplasticity.